Odpowiedzi

2009-11-26T15:07:08+01:00
A) 0,3c³-0,2c²-0,6c³+c² = - 0,3c³ + 0,8c²
b) 5d²-1,5d³-½d²-0,8+d³-2,2 = -0,5d³ + 4,5d² -1
c) 3ab-5a²b²-6ab²+2ab+ab²+7a²b² = 2a²b² -5ab² + 5ab
d) 13a²bc+8abc²-12a²bc-2abc²+5a²bc = 6a²bc + 6abc²

1 5 1
2009-11-26T15:14:16+01:00
A) 0,3c³-0,2c²-0,6c³+c² = -0,3³ + 0,8c² (podkreślamy wyrazy podobne i je redukujemy)

b)5d²-1,5d³-½d²-0,8+d³-2,2 = 4½d² - 0,5d³ + 1,4 (tu tak jak w poprzednim przykładzie)

c) 3ab-5a²b²-6ab²+2ab+ab²+7a²b² = 5ab + 2a²b² - 6ab² (tu także)

d) 13a²bc+8abc²-12a²bc-2abc²+5a²bc =a²bc + 6abc² + 5a²bc =
= 6a²bc + 6abc² (oczywiście tu też)
1 5 1
2009-11-26T16:40:56+01:00
A) 0,3c³-0,2c²-0,6c³+c² = - 0,3c³ + 0,8c²
b) 5d²-1,5d³-½d²-0,8+d³-2,2 = -0,5d³ + 4,5d² -1
c) 3ab-5a²b²-6ab²+2ab+ab²+7a²b² = 2a²b² -5ab² + 5ab
d) 13a²bc+8abc²-12a²bc-2abc²+5a²bc = 6a²bc + 6abc²